Association between Dental Caries and Body Mass Index (BMI) among Adolescents in Urban Area of North-Western Bangladesh - Akram Hossain; Mohammad Razib Mustafiz (Universitas Muhammadiyah Metro, 2026)
This cross-sectional study aimed to investigate the potential association between body mass index (BMI) and dental caries (DMFT) in adolescents aged 12-16 years in Rangpur, Bangladesh. A total of 300 students participated in the study. Dental caries prevalence was assessed using the DMFT index, and BMI was calculated according to standardized protocols. Socioeconomic status, sugar consumption, and physical activity levels were also captured through questionnaires. Statistical analysis employed multivariate logistic regression and linear regression models to explore the relationships between BMI, dental caries, and other factors. Dental caries (DMFT > 0) was present in 54.1% of participants, while 32% were classified as overweight or obese. A statistically significant positive correlation was observed between BMI and DMFT (P = 0.008). Compared to those within the normal BMI range, obese participants were 1.79 times more likely to exhibit healthy teeth (DMFT = 0) (P = 0.02). Higher socioeconomic status (P = 0.005) and fluoridated toothpaste use (P = 0.02) were also associated with a greater likelihood of healthy teeth. Physical activity displayed a significant negative association with BMI (P < 0.001). This study demonstrated a positive association between BMI and dental caries in Rangpuri teenagers. Interestingly, obese participants were more likely to have healthy teeth, potentially signifying the influence of sociodemographic factors and oral hygiene practices in mitigating caries risk. The study highlights the importance of considering socioeconomic context and preventive measures while addressing the link between obesity and dental health in this population.